ПРОБЛЕМА ІСТОРИЧНОГО ФАКТУ В КЛАСИЧНІЙ, НЕКЛАСИЧНІЙ ТА ПОСТНЕКЛАСИЧНІЙ НАУЦІ (Zaporizhzhia Historical Review, 2021)
The article finds contradictions in the traditional approaches to historical fact within the framework of such categories as personality–impersonality, continuity–non-continuity, homogeneity–heterogeneity and coherence– non-coherence. The author comes to the conclusion, that application of N.Luhman’s sociological theory removes these contradictions and provides room for major civilizational research ventures in history.